Effective presentation - Dickinson, Sarah. (Orion, 1998)
The art of public speaking. Where do you start? Your audience. Think before you write. Avoiding verbal pitfalls. Giving life to your speech. Visual and other aids. Controlling your nerves. The performance. How to answer questions and deal with interruptions. How to be interviewed by the media. How to hold a press briefing.